1996
DOI: 10.1179/joc.1996.8.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sulbactam-Ampicillin for the Treatment of Severe Diabetic Foot Infections

Abstract: Diabetic foot infections, a frequent and serious cause of morbidity in patients with diabetes mellitus, are caused by anaerobic and aerobic bacteria. Given the fact that seriously impaired host defense factors are almost always present in these patients, bactericidal agents with a broad spectrum of antimicrobial activity are required for their treatment. Seventy-four patients with diabetic foot infections were treated with parenteral sulbactam-ampicillin (1.5 g, q.i.d.). All patients were followed-up prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Intravenous antibiotic therapy of ampicillin sulbactam has been shown to be safe and effective in the treatment of diabetic foot infections (11) and our hospitalized patients received the empirical therapy of ampicillin sulbactam, 4 g per day for at least 7 days prior to undergoing any type of diabetic foot surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Intravenous antibiotic therapy of ampicillin sulbactam has been shown to be safe and effective in the treatment of diabetic foot infections (11) and our hospitalized patients received the empirical therapy of ampicillin sulbactam, 4 g per day for at least 7 days prior to undergoing any type of diabetic foot surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Agents that have demonstrated clinical effectiveness, alone or in combination, in prospective studies including entirely or mostly patients with diabetic foot infections, include the following [51]: cephalosporins (cephalexin orally; cefoxitin and ceftizoxime parenterally) [10,[52][53][54][55][56]; penicillin/b-lactamase inhibitor congeners (amoxicillin/clavulanate orally; ampicillin/ sulbactam, piperacillin/tazobactam, and ticarcillin/clavulanate parenterally) [57][58][59][60][61]; fluoroquinolones (ciprofloxacin, ofloxacin, levofloxacin, and trovafloxacin orally and parenterally) [57,[61][62][63][64][65]; and the miscellaneous agents clindamycin (orally and parenterally) [10,63,65], imipenem/cilastatin (parenterally) [58,66], amdinocillin (parenterally) [55], linezolid (orally and parenterally) [67], and pexiganan acetate (topically) [50].…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…High rates of clinical cure using ampicillin-sulbactam have also been reported by Akova et al [32] in a study of 74 diabetic patients with severe foot infections, 25 of whom had soft-tissue infections and 49 of whom had osteomyelitis. After treatment for 14 days with parenteral ampicillin/sulbactam, 100% of patients with soft-tissue infections were cured.…”
Section: Diabetic Foot Infectionsmentioning
confidence: 64%
“…The ␤-lactam/␤-lactamase inhibitor combinations possess a good safety and tolerability profile and an antimicrobial spectrum that encompasses both aerobic and anaerobic organisms. Recent clinical studies have shown that these agents are appropriate for the initial empiric and definitive parenteral therapy of diabetic foot infections, and are well tolerated when given for long periods [31,32]. A comparative, double-blind trial was conducted in which 96 diabetic patients with limbthreatening foot infections were randomized to treatment with either ampicillin/sulbactam or imipenem/cilastatin [31].…”
Section: Diabetic Foot Infectionsmentioning
confidence: 99%